Analysis of Factors Influencing Labor Absorption in the Woven Fabric Industry in the Pringgasela Region, East Lombok Regency - M Reza Wira Rafsanjani; St Maryam (Future Techno-Science, 2026)
This study aims to analyze the influence of business income, business capital, wages, and age of the workforce on labor absorption in the woven fabric industry in Pringgasela Village, East Lombok Regency. Data were collected using questionnaires distributed to weaving artisans. The research method used was a quantitative method with a descriptive approach with multiple linear regression analysis techniques. Data processing was carried out using Eviews 12 software, with hypothesis testing using the F test (Simultaneous) and T test (Partial). The results of this study partially show that business income, wages, and age of the workforce have a positive and significant effect on labor absorption. While the business capital variable has a negative and insignificant effect on labor absorption. Simultaneously, these four variables also have a significant effect on increasing labor absorption in the woven fabric industry in Pringgasela. This study shows that increasing income, providing appropriate salaries, and the presence of more workers in productive age are factors that encourage the increase in the number of workers. Meanwhile, business capital has not been proven to directly affect the ability of artisans to add workers. This research is expected to serve as a reference for local governments and business actors in planning strategies for developing the woven fabric industry.